ANALISIS HUBUNGAN MODAL SOSIAL DAN TINGKAT KEBERDAYAAN PETANI KELAPA SAWIT DI DESA SUKAMAJU KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Ani Lisnawati; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims : analyze social capital of oil palm farmers, analyze the level of empowerment, analyze the relationship between social capital and the level of empowerment. This researsch uses a purposive sampling method with respondents consisting of 80 members of farming group. Data collection method in this research is primary and secondary data. To determine the social capital in this research using a quantitative method using a questionnaire in the form of likert scale. From the research data showed (1) social capital of oil palm farmers Sukamaju Village Tapung Hilir Subdistric Kampar Regency is high with score average is 3.51. (2) level of empowerment of oil palm farmers in Sukamaju Village Tapung Hilir Subdistric Kampar Regency in high with average score is 3.44. (3) the relationship of social capital and level of empowerment is significant weak until strong with rs = 0.683 and value of p ( p < 0,05 ). Means that the higher the level of empowerment that is the higher the social capital of oil palm farmers. Keywords: Social Capital, Empowerment, Farmers